Comparative study on composting of single and mixed food waste using black soldier fly larvae (HERMETIA ILLUCENS) / Muhammad Firdaus Saidatulakmar - Saidatulakmar, Muhammad Firdaus (2023)
The demand for effective organic waste management and expanded global food production has grown in tandem with the rapid urbanisation and population expansion of our planet. Organic waste, including food waste, is typically disposed of by anaerobic digestion, landfill disposal, or cremation; however, more ecologically friendly treatment options are required. Due to its low cost and little impact on the environment, the use of Black Soldier Fly (Hermetia illucens) larvae (BSFL) to treat organic waste is becoming more prevalent. BSFL has the amazing capability to reduce a broad range of wastes while simultaneously producing feed for people or animals, and the organic fertiliser it produces has a high nutritional content, including oils and protein. Researched below are the bioconversion methods used by black soldier fly larvae (Hermetia illucens) and their efficacy in treating food waste. It is based on the effects of single and combined food waste. We discuss how BSFL's grow under ideal conditions and how waste treatment processes affect their progress. Laboratory study of each sample revealed the factor affecting BSFL's efficiency in transforming food waste into organic fertiliser. According to studies, the largest amount of bio-compost may be produced from mixed food waste (Large). Compost made from large quantities of food scraps meets all specifications for compost in terms of pH, electrical conductivity, and moisture content. Tapioca pulp waste, however, had the greatest nutritional content in the BSFL, especially in the forms of protein and lipids that are useful in animal feed.